ANALISIS DAMPAK SOSIAL-EKONOMI TERHADAP AKSES PENDIDIKAN BAGI ANAK-ANAK MASYARAKAT ADAT PROVINSI PAPUA - Rahayu Ningsih, Sri; Zakiah , Linda; Salsabilla , Reiva; Hartati, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Poverty, income inequality, and limited education infrastructure are the main obstacles that make it difficult for children in Papua to access proper education. This research aims to analyze the socioeconomic impact on indigenous Papuan children's access to education. This research uses a qualitative method through a literature study approach. Data were obtained from academic books related to the variables and scientific articles in national journals, with the criteria of being published in the last 10 years and relevant to the variables. The data collection technique used was data-based searches on the internet, and systematically reviewed and grouped by variable. The analysis was carried out using the content analysis method by analyzing themes, patterns, and relationships between variables from the content of the literature. Data validity and reliability were tested using source triangulation. The results show that socio-economic conditions greatly impact access to education for indigenous children in Papua.